KONSISTENSI KEBIJAKAN KANTOR PERTANAHAN DALAM MENSEJAHTERAKAN PETANI MISKIN - Budhiawan, Haryo; Nugroho, Aristiono (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
To make poor inhabitants obtain welfare is a joint effort of various institutions together with the poor themselves. The task will fail if the interanalisation of interest does not exist. The poor farmers’ welfare is not only the interest of the farmers themselves but should also be the interest of the land office. This will result if the land office is consistent in empowering the farmers. What kind of consistency does the land office own at present? The reply can be obtain through a qualitative rationalistic research. All of the answers were done through interniews of the informants and library study. The forms of consistency of the land office were defending the opinions, seeking for the funds, and persuading people..The forms of consistency found in village government the efforts of the village head on preserving the environment. For the poor, the consistency they wanted was that their certificates of land ownership to be used as an asset for their future business. Key words: consistency, policy, farmers’ welfare